کێشەكانی هاوڕێی ڕەخنەگر لەخوێندنگە بنەڕەتیەكانی شاری سلێمانی لەدیدی خۆیان و مامۆستایانەوە (توێژینەوەی هەڵێنجراو) - حمە, ئەحمەد علی; امین, عبداللە كریم; حمەرشید, هاوار مولود (Sulaimani Journal for Humanities, 2023)
The aim of the study was to measure the issues (knowledge, skills, values and behavior, management, artistic, personal) from the perspective of critical friend and teachers, to know the differences in the views of critical friend and teachers about the issues (knowledge, skills, values, and behavior, management, artistic, personal) according to the variables (gender and expertise), to achieve the objective of the research, the researcher used the method (analytical description), the research community is specific to the first variable (teachers), the researcher relied on the method (analytical description) that is appropriate to the content of the research. The researcher included critical friends and primary school teachers from both education directorates (east and west) of Sulaymany as the research community. In this community, the sample for the first variable (teachers) in both directorates (East and West) was (352) teachers of both sexes (male and female), the sample for the second variable (critical friend) was only (91) persons has been randomly identified as the critic friend, of both sexes (male and female.His research tool included preparing a survey form for the Fields of (knowledge, skills, values and behavior, management, artistic, personal) which has been divided into his research sample, which included (teachers and critical friends) Finally, according to the purpose of the research he has been come to a conclusion of , which was to measure the problems (knowledge, skills, values and behavior, management, artistic, personal) from the perspective of critical friends and teachers, and differences in the views of critical friends on problems like (knowledge, skills, values and behavior, management, artistic, personal) according to the variables (gender, expertise) The study achieved its objectives, i.e. according to the methods presented in the third part of the study.